1992
DOI: 10.1213/00000539-199202000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Response Time of Pulse Oximeters Assessed Using Acute Decompression

Abstract: In human volunteers, the response times of 11 pulse oximeters to a 10% step reduction in arterial oxygen saturation were measured using an acute decompression technique. When finger probes were used, nine oximeters had similar response times and two were significantly slower (P less than 0.05). The ear probe response time was similar on six oximeters assessed, and faster than the finger probes. The response times of the oximeters to an acute increase in arterial saturation were tested by suddenly changing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Severinghaus and Naifeh 19 found the response times at the ear or finger for step desaturation to be longer than for step resaturation. Young et al 20 reported a noticeably slower response with probes at the finger, compared with the ear. Finally, Reynolds et al 21 specifically examined pulse oximetry kinetics in relation to probe site placement in children with congenital heart disease and reported significant differences for cheek versus finger or toe during desaturation and resaturation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Severinghaus and Naifeh 19 found the response times at the ear or finger for step desaturation to be longer than for step resaturation. Young et al 20 reported a noticeably slower response with probes at the finger, compared with the ear. Finally, Reynolds et al 21 specifically examined pulse oximetry kinetics in relation to probe site placement in children with congenital heart disease and reported significant differences for cheek versus finger or toe during desaturation and resaturation.…”
Section: Discussionmentioning
confidence: 98%
“…The impact of probe site placement on SpO 2 accuracy and response time has been previously investigated. 5,15,[17][18][19][20][21] Iyer et al 5 reported no difference between hand and foot probe sites in infants less than 3 months of age undergoing cardiac surgery with cardiopulmonary bypass. Warley et al 18 described finger and toe response time to be proportionately longer than ear probe response in normal subjects and attributed this finding to increased lung to periphery circulation times.…”
Section: Discussionmentioning
confidence: 99%
“…We attribute this to the warming of the measurement side resulting in an increased local perfusion and, hence, well-defined pulsatile signals [20]. In the present study in the peripherally well-perfused patients, the faster response time with regards to the SpO 2 values at the ear versus left index finger by an average of 30 s is mainly site related [22]. In patients with peripheral vasoconstriction or low perfusion the time lag between ear and finger sensor readings would even be larger.…”
Section: Discussionmentioning
confidence: 80%
“…The response time ofoximeter probes was assessed by Severinghaus and Naifeh [17] who induced 30-60s hypoxic plateaus between anS a O 2 of 40 and 70% in healthy volunteers.Oximeter probes placed on the ear generally had a much faster response to asudden decrease in fractional inspired oxygen concentration(F i O 2 ) than did the finger probes (10-20 versus24-35s, repectively). Employing hypobaric facility to induce hypoxia in normalvolunteers, Young et al [21] also observedthat the response time of the finger probes were slower than the ear probes inresponse to either a decrease or increase in O 2 saturation.…”
Section: Accuracymentioning
confidence: 99%